A Questionnaire Based Study on Awareness of Sanitization of Tooth Brushes in Indian Population and Their Disinfection with an Oral Hygiene Aid Sterilizer: A Clinical and In-Vitro Study. - Patil, Dr. Chitra Laxmikant; Ghodke , Dr.Monali; Redkar, Dr.Gaurav; Dedhia, Dr.Maitri; Pal, Dr.Poulomi; Jain, Dr.Devi (International Journal of Scientific Research and Management (IJSRM), 2024)
Abstract: Oral  diseases  are  a  major  public  health  concern,  owing  to  their  high   prevalence  and  their  relationship  with  systemic  health. Oral  health  maintenance  can   only  be  accomplished  with  proper  tooth  brushing  &  tongue  cleaning. Toothbrushes  are  kept  in  places  which  is  a  hub  of  contaminants. They  should   be  correctly  stored, disinfected  and  changed  at  regular  intervals.Aims: Our  study  focuses  on  awareness  of  disinfection  of  toothbrushes  among general  population  and  invention  of  a  newer  device  that  not  only  keeps  the  toothbrush  moisture  free  but  also  germ  free:  Oral  Hygiene  Aid  Sterilizer  (OHA-S).Methods and Material: A  cross  sectional  questionnaire  based  study  of  sample  size  100  was  conducted  in  which  samples  were  randomly  selected  and  distributed  with  a  questionnaire  form. All  the  study  participants  were  asked  to  brush  their  teeth with  the  tooth  brush  provided. After  brushing,  the  contaminated  bristles  were  disinfected  in  the  newer  device: OHA-S  and  were  observed  under  phase  contrast  microscope.Statistical analysis used: Randomized  control  trialResults: Survey  results  showed  that  61%  of  general  population  was  unaware  of  sanitization  of  toothbrushes.  The  remaining  being  aware,  almost  72%  did  not  perform  sanitization  on  daily  basis.  Also,  there  was  a  significant  decrease  in  microbial  flora  of  the  bristles  which  were  sanitized  using  OHA-S  when  observed  under  the  phase  contrast  microscopeConclusions: As  majority  of  population  failed  at  sanitizing  oral  hygiene  aids  daily, OHA-S  was  effective  in  not  only  making  the  oral  hygiene  aids  moisture  free  but  also  in  reducing  the  amount  of  microbial  load  which  is  the  main  causative factor  for  periodontal  diseases .